A phase I–II study on the combination of rapamycin and short course radiotherapy in rectal cancer. Issue 2 (August 2015) - Buijsen, Jeroen; van den Bogaard, Jørgen; Jutten, Barry; Belgers, Eric; Sosef, Meindert; Leijtens, Jeroen W.A.; Beets, Geerard L.; Jansen, Rob L.H.; Riedl, Robert G.; Clarijs, Ruud; Lammering, Guido; Lambin, Philippe
Abstract: Purpose: This phase I/II study sought to determine the safety and maximum tolerated dose (MTD) of the combination of rapamycin, an mTOR inhibitor, with short-course radiotherapy in rectal cancer patients. Antitumor activity, changes in metabolic activity and perfusion on imaging, and changes in phosphorylation status of the mTOR pathway were also assessed. Materials and methods: Patients with primary resectable rectal cancer were treated with short-course hypofractionated radiotherapy (5 × 5 Gy) combined with oral rapamycin 1 week before and during radiotherapy, followed by surgical resection. Results: Thirteen patients were entered in phase I. One patient developed a dose-limiting toxicity, consisting of a grade 4 leak and grade 4 bleeding. Because of an unexpected high rate of grade 3 postoperative toxicity, it was decided to treat patients with delayed surgery in phase II. Primary endpoint for phase II was tumor blood flow ( K trans ) assessed by perfusion CT. Thirty-one patients were treated with the MTD of 6 mg rapamycin daily. One patient (3%) developed a pathological complete response (pCR) and 3 patients (10%) had a ypT1N0 tumor at the time of resection. No change in tumor perfusion was observed on perfusion CT, but a significant decrease of metabolic activity was found on PET-scan. Conclusions: The combination of short-course radiotherapy and rapamycin turned out to be feasible, provided that the interval between neo-adjuvant treatment and surgical resection is at least 6 weeks. Although from this cohort no clear increase in pCR could be observed, a clear metabolic response after rapamycin run-in was observed, indicating a biological activity of this drug in rectal cancer.